2017
DOI: 10.1016/j.aorn.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Implementation: Positioning the Patient

Abstract: Every surgical procedure requires positioning the patient; however, all surgical positions are associated with the potential for the patient to experience a positioning injury. The locations and types of potential injuries (eg, stretching, compression, pressure injury) depend on the position. Factors that may increase the patient's risk for an injury are the length of the procedure and risk factors inherent to the patient (eg, weight, age, frailty). AORN's updated "Guideline for positioning the patient" provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
23

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 24 publications
(50 reference statements)
0
40
0
23
Order By: Relevance
“…Donut-shaped gel head supports are typically made of gel materials and are used to protect the head, neck, and ears during motionless treatments by off-loading the occiput, often in the OR during surgical procedures conducted in supine patients, as well as during recovery from operation or in the ICU. 8,9 In the present work, we compared the state of mechanical loads in scalp tissues of the occipital region while using a donut-shaped gel head support, a Z-Flo head positioner, or a standard medical foam support for the same virtual adult head using our FE modelling framework, which was validated against pressure mapping. Our results demonstrated that a standard, flat medical foam is more successful than a donut-shaped gel head support in dispersing scalp tissue loads, but the foam is still limited in conformability relative to the Z-Flo fluidised positioner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donut-shaped gel head supports are typically made of gel materials and are used to protect the head, neck, and ears during motionless treatments by off-loading the occiput, often in the OR during surgical procedures conducted in supine patients, as well as during recovery from operation or in the ICU. 8,9 In the present work, we compared the state of mechanical loads in scalp tissues of the occipital region while using a donut-shaped gel head support, a Z-Flo head positioner, or a standard medical foam support for the same virtual adult head using our FE modelling framework, which was validated against pressure mapping. Our results demonstrated that a standard, flat medical foam is more successful than a donut-shaped gel head support in dispersing scalp tissue loads, but the foam is still limited in conformability relative to the Z-Flo fluidised positioner.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Head positioning, specifically, is required for maintaining midline and/or the chin upwards, for immediate access to the airways in an anaesthetised, ventilated patient, as well as for the distribution of head loads at the occipital region in the supine posture. 8,9 Common positioning techniques that nursing teams are employing often include the use of items that are not specifically designed for the purpose of therapeutic positioning, such as rolled towels and blankets that flatten and will not maintain a set position, and may also heat up. 8 Dedicated head supports also exist.…”
Section: Introductionmentioning
confidence: 99%
“…This could be possibly due to the unsuitability of operating table length for tall people, which causes their ankles to hang off the bed and puts excess pressure on their skin. Therefore, it is recommended to place a proper pad where the patient's ankles hang off the operating table (34).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery specific positioning protocols should be integrated into surgical checklist to decrease positioning injuries. 67…”
Section: Intraoperative Considerations Patient Positioningmentioning
confidence: 99%